Integration between Management Capability and Relationship Capability to Boost Supply Chain Project Performance - Yuliadi, Boy; Nugroho, Andi (ExcelingTech, 2019)
— In the current decade, supply chain companies are focusing on project management to increase the performance. The companies are struggling with different issues related to the project management. These issues have adverse effect on supply chain project performance. The important issues include; information communication technology (ICT), management capabilities and relationship capabilities. However, these issues can be resolved with the help of information communication technology (ICT). Therefore, the objective of this study is to examine the role of information communication technology (ICT) in supply chain project success. To achieve this objective, primary data is collected from supply chain companies in Indonesia. The employees of these companies were communicated to get data. For this purpose, a survey was carried out in which survey instrument was used for data collection. Results of the study demonstrated that information communication technology (ICT) has the ability to decrease various issues such as management capabilities and relationship capabilities and promote supply chain project success. Information communication technology (ICT) helps to transfer the possible effect of management capabilities and relationship capabilities on supply chain project performance.